Addressing the Aging Process Through the Ayurveda Lifestyle Interventions and Adaptations (International Journal of Ayurveda and Pharma Research, 2024)
The elderly population is growing worldwide, leading to an increased focus on geriatric care and promoting healthy aging. Ayurveda, an ancient Indian system of medicine, offers a holistic approach to healthcare that can be beneficial for addressing the unique needs of older adults. This research article explores the integration of geriatrics and Ayurveda, highlighting the potential benefits of Ayurvedic principles, lifestyle adaptations, and herbal remedies in geriatric care. By combining the wisdom of Ayurveda with modern geriatric practices, healthcare providers can offer comprehensive and personalized care to elderly individuals, enhancing their quality of life and promoting healthy aging. The field of geriatrics focuses on the healthcare needs of older adults, aiming to promote physical, mental, and emotional well-being in the elderly population. This study focus on enhancing the concept of geriatrics through the principle of Ayurveda related to lifestyle management. To minimize the functional decline and to enhance the quality of life in geriatric age group through the incorporation of Ayurveda lifestyle adaptation is the main goal of this paper. Lifestyle diseases are related with the people’s way of living. This is generally caused by lack of physical activity and unhealthy food habits. A healthy lifestyle must be adapted to fight the various age related disorders and diseases. Ayurvedic principles of health and disease focus on the concept of three Doshas: Vata, Pitta and Kapha. These are the three forces that determine the functioning of the body and mind. Although every person has all three Doshas, ​​we will each inherit them differently. This is responsible for the differences in our characters, likes, dislikes, attitudes and behaviours.